Organización administrativa del centro educativo comunitario intercultural bilingüe “muyu kawsay” en el periodo 2015 – 2018” propuesta estrategia de dinámica organizacional. - Freire Prado, José Alfredo (2017)
The lack of organizational dynamics in the Muyu Kawsay Bilingual Intercultural Community Education Center affects the teaching-learning process, disrupting the teaching development, and causing conflicts with the rest of the members of the educational community. The disorganization in the educational center to improve the organizational dynamics and develop an adequate educational administration. For those of us who work in education, not only hard work is necessary but also in an intelligent and organized way, for this reason it is proposed to carry out a strategic planning that will help to solve the actions within the educational organization. It will improve institutional objectives, strategies and operations, always trying to anticipate changes and adapting plans according to need.